Cecocolic Intussusception in an Asian Elephant (Elephas maximus) in Sri Lanka Associated with Chronic Hepato-Intestinal Schistosomiasis: A Case Report - Karawita, A.C.; Rajapakse, R.C.; Amarasiri, P.G.I.D.; Ramanayake, R.M.T.M.; Jayaweera, W.R.; Bollinger, Trent K.; Gunawardena, G.S.P.De.S. (International Journal of Applied Sciences and Biotechnology, 2015)
A 25 year old female captive Asian elephant weighing approximately 3000kgs died and was subjected to a complete necropsy within 5 hours post mortem. Grossly, the elephant had sub-cutaneous edema, cecocolic intussusception and ascites. Histopathological examination revealed multifocal, granulomatous, portal phlebitis in the liver, multifocal, granulomatous, peri-portal hepatitis with marked portal and perisinusoidal fibrosis, and multifocal granulomatous colitis with intralesional Schistosoma eggs. To our knowledge, this is the first report of cecocolic intussusception in an Asian elephant associated with Schistosoma infection. Int J Appl Sci Biotechnol, Vol 3(4): 744-746